One exercise session a day keeps the physio away: effect of a newly designed daily exercise programme on injury prevention in youth football - A randomised controlled trial - Brunelli, M.; Brunelli, G.; Wilson, C.; Delahunt, E.; Nutarelli, S. (Physical Therapy in Sport, 2025)
Objectives To compare the effect of a newly conceived daily injury prevention programme with FIFA11+ on injury incidence and severity in academy football players.